The Effect of Acacia mangium Leaf Feed on Apparent Metabolizable Energy, Growth Performance, and Carcass Composition of Broiler Chickens - Saichon Lerdsuwan; Warrapong Nalinanon; Duangjai Pisuttharachai (ASEAN Journal of Scientific and Technological Reports, 2022)
The experiments were conducted to determine the apparent metabolizable energy of Acacia mangium leaf meal (AMLM) and the effect on growth performance and carcass composition of broiler chickens (Arbor acres). Twenty-four broiler chickens at the age of 24 days were divided into 2 groups with four replications of two chickens raised individually in a cage. The apparent metabolizable energy of AMLM-feeding chicken was 2,359.90 kcal/kg. Experimental diets consisted of AMLM 0%, 2.5%, 5%, 7.5%, and 10% feeding for 161 one-day-old unsexed broiler chickens and were randomly assigned to five groups with four replications of eight chickens in a completely randomized design. Feed and water were offered ad-libitum throughout the experimental period. At the age of 45 days, 2 broilers per replicate were slaughtered, and the carcass was determined. The results indicated that broiler chickens fed AMLM diets were not significantly different in weight gain, average daily gain and feed intake compared to the control diet (P>0.05). But chickens fed AMLM had decreased feed conversion ratio than the control (P<0.05). In addition, broiler chickens fed AMLM diets were not significantly different in all carcass composition parameters compared to the control diet (P>0.05). It is concluded that the AMLM contained 10% in diets does not affect broiler chickens' growth performance and carcass composition.
Keywords: Animal Nutrition and Physiology; Ginger and Zingiberaceae research; Mangiferin and Mango Extracts